Association between psychosocial interventions and aberrant salience in adolescents with early psychosis: A follow‐up study. Issue 4 (14th March 2022) - Poletti, Michele; Pelizza, Lorenzo; Azzali, Silvia; Scazza, Ilaria; Paterlini, Federica; Garlassi, Sara; Chiri, Luigi Rocco; Pupo, Simona; Raballo, Andrea
Abstract : Although aberrant salience (AS) is a putative vulnerability factor in schizophrenia, empirical research on AS in early stages of psychosis is currently relatively scarce (especially as regards on its longitudinal course and treatment response in adolescence). The aim of the present study was to longitudinally monitor the stability of AS along a 1‐year follow‐up period in an Italian population of community help‐seeking adolescents with First Episode Psychosis (FEP) or at Ultra‐High Risk (UHR) of psychosis and to examine any relevant association of AS with specific treatment components of a specialized "Early Intervention in Psychosis" (EIP) program across the 1 year of follow‐up. Participants (38 FEP, 42 UHR), aged 13–18 years, completed the Comprehensive Assessment of At‐Risk Mental States (CAARMS) and the Aberrant Salience Inventory (ASI) both at baseline and at the end of the follow‐up period. Spearman's correlations between AS scores and specific EIP treatment components were performed. After the 1 year of follow‐up, both FEP and UHR adolescents showed a statistically significant reduction in AS levels. In FEP patients, this was correlated to the number of psychoeducational sessions provided to their family members. In the UHR subgroup, this AS decrease was associated with the number of individual Cognitive‐Behavioral Therapy (CBT) sessions directly offered to help‐seeking adolescents. AS is relevant both in FEP and UHR adolescents already at the enrollment in specialized EIP programs. However, its longitudinal levels decrease over time, together with the delivery of specific psychosocial EIP interventions.